The Role of Executive Functions in Improving Narrative Text Writing Skills: Analysis at The Macro and Micro Levels of Text Structure - Dewi, Ria Candra; Yanti, Prima Gusti; Tarmini, Wini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This research is motivated by the low ability of students in writing and their difficulty in expressing ideas in written form. This study aimed to investigate the role of executive functions on students' narrative text-writing skills. The research method used a factorial analysis design to determine which executive functions contributed the most to students' narrative writing skills. The participants of this study were 150 high school students aged 9-12 years. Data collection was carried out through several tests. The tests assessed transcription skills, language skills, and executive functions involved in the student's writing process using the CLAN test, Mean Length of T-unit in words (MLTUw), and ERRNI. The data analysis used multiple regression analysis. The study results showed that these executive functions contributed directly and indirectly to students' narrative writing skills. The aspects of constraints, including planning, contributed directly to the long and short aspects of the text. In addition, the aspects of constraints and renewal indirectly affected the length of the text, the level of sentence complexity, and the quality of the story content. This study implies that a teacher must be able to optimize executive functions, namely planning, revising, and reviewing students' abilities through various writing strategies or methods. Developing this executive function is very beneficial for students in improving their writing skills, especially in writing literary texts.